Effects of NaCl on Seed Germination and Growth of Yam Bean (Pachyrhizus erosus (L.) Urb.) Using a Hydroponic Technique - ชูกำแพง, ผู้ช่วยศาสตราจารย์ ดร.สุมาลี; จัตุรัส, ปัทมา (Journal of Food Health and Bioenvironmental Science, 2017)
The objective of this study was to determine the effects of salinity on seed germination and the growth of yam bean (Pachyrhizus erosus (L.) Urb.) by a hydroponic technique, utilizing Hoagland’s solution with NaCl. Yam bean seedlings were germinated in a sponge for 14 days. The plants were hydroponically grown in the solution for 21 days followed by treatments of 0, 50, 100 and 200 mM for 60 days. The observed effects of salinity were decreasing seed germination, fresh weight, dry weight, number of shoots and number of roots with increasing sodium chloride concentrations.